THE INFLUENCE OF PERCEIVED USEFULNESS, EASE OF USE, COMPATIBILITY AND RISK ON MOBILE BANKING USER ATTITUDE (Study at PT. Bank Rakyat Indonesia Tbk. Branch Malang Kawi) - Restu Andhi Ardana (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
This research has the background to know implementation use of Mobile Banking in PT Bank Rakyat Indonesia. The purpose of this research is to know how the influence of Perceived Usefulness, Ease of Use, Compatibility, and Risk On Mobile Banking User Attitude PT Bank Rakyat Indonesia Malang Kawi. Type of this research can be considered as explanatory research with the hypothesis testing and this study is using accidental sampling technique where the use criteria are all customers that using mobile banking facility that amount 96 person. The result can be seen that positive effect between usefulness, ease of use, compatibility, risk variables on mobile banking user attitude it can be seen the F equal to 22.028 with a Fsignificance equal to 0.000 (p<0.05). There are usefulness variable who has a influence dominant, proved with has highest coefficient beta 0,291 and t 2,987 as well as value of probability 0,004 (p<0,05). While known amount of the effect of four variables simultaneously on mobile banking user attitudes as seen fromadjusted R square value 0,470 the value indicates that each variable contributed respectively 47% to mobile banking user attitude. While 53% were influenced by other variables not examined in this study.Keywords: Usefulness, Ease of Use, Compatibility, Risk, User AttitudeAbstrakPenelitian ini mempunyai latar belakang untuk mengetahui bagaimana implementasi penggunaan Mobile Banking di PT Bank Rakyat Indonesia. Tujuan dari penelitian ini untuk mengetahui bagaimana pengaruh Persepsi Kegunaan, Kemudahan Penggunaan, Kesesuaian, dan Risiko Pada Sikap Pengguna Mobile Banking studi di PT Bank Rakyat Indonesia Cabang Malang Kawi. Jenis penelitian ini adalah penelitian penjelasan dengan pengujian hipotesis dan metode pengumpulan sampel dalam penelitian ini menggunakan teknik accidental sampling dimana kriteria penggunaan semua nasabah yang menggunakan fasilitas mobile banking yang berjumlah 96 orang. Dari hasil penelitian dapat diketahui bahwa pengaruh positif antara kegunaan, kemudahan penggunaan, kesesuaian, dan risiko berpengaruh pada sikap pengguna mobile banking dapat dilihat dari nilai F 22,028 dengan signifikansi F sebesar 0,000 (p<0,05), Selain itu, variabel kegunaan yang memiliki pengaruh paling dominan, terbukti dengan memiliki koefisien beta tertinggi yaitu 0,291 dan t 2,987 serta nilai probabilitas 0,004 (p<0,05). Sementara diketahui jumlah pengaruh dari empat variabel secara simultan ke sikap pengguna mobile banking seperti yang terlihat dari Adjusted R Square dengan nilai 0,470 menunjukkan bahwa tiap variabel memberikan kontribusi masing-masing sebesar 47% terhadap sikap pengguna mobile banking. Sementara 53% dipengaruhi oleh variabel lain yang tidak diteliti dalam penelitian ini. Kata kunci : Kegunaan, Kemudahan Penggunaan, Kesesuaian, Risiko, Sikap Pengguna